The relationship between muscle stem cells and motor neurons. - Zmojdzian, M.; Jagla, K. (Cellular and molecular life sciences. CMLS, 2021)
Neuromuscular system is constituted of multi-fibrillar muscles, tendons, motor neurons and associated muscle stem cells. Stereotyped pattern of muscle innervation and muscle-specific interactions with tendon cells suggest that neuromuscular system develops in a coordinated way. Remarkably, upon regeneration, coordinated assembly of all neuromuscular components is also critical to rebuild functional muscle. Thus, to ensure muscle function, the neuromuscular system components need to interact both during development and regeneration. Over the last decades, interactions between muscles and tendons, muscles and motor neurons and between muscles and muscle stem cells have been extensively analysed and documented. However, only recent evidence indicates that muscle stem cells interact with motor neurons and that these interactions contribute to building functional muscle both during development and regeneration. From this perspective, we discuss here the relationship between muscle stem cells and motor neurons during Drosophila neuromuscular system development and adverse impact of affected muscle stem cell-motor neuron interactions in regenerating vertebrate muscle.